ANALISIS METODE KANBAN DAN METODE JUNBIKI PADA PERSEDIAAN PART MUFFLER DI PT. XYZ - Edi Susanto; Afriandy Barus (Teknoin, 2016)
PT. XYZ is a company main business automotive manufacturing. In producing the vehicle , the company uses a wide variety of parts , and which are part muffler . In the storage part mufflers require a fairly wide area , because there are 4 types of parts muffler with the same amount of container that is used pallet containing 30 pcs to be stored in accordance with the indications of the respective part . Part muffler having too much stock so that the buildup . When supply process takes a long time and area inventory requires a large area and that a lot of man power. In a problem that occurs in PT. XYZ, the authors analyze and compare methods that have been applied, the Kanban method and Junbiki method, where the two systems will produce a comparison in terms of man power requirements ( labour ), work time and inventory area. With Junbiki method which has the concept of zero inventory, then the result analysis shows that by using the Junbiki method to the needs of area per period can be reduced 91 % , labor requirements can be reduced by 20 % and for a time requirement handling and supply can be reduced by 22%, The research proves that Junbiki method better than the kanban method.